Bariatric / obesity surgery - Buchwald, Henry (Henry Stewart Talks, 2007)
The evolution of bariatric surgery procedures, Jejunoileal bypass, Modern malabsorptive procedures, Biliopancreatic diversion of Scopinaro, Modification of the biliopancreatic diversion to a duodenal switch, Gastric bypass, Fobi procedure, Laparoscopic Roux gastric bypass, Vertical banded gastroplasty, Laparoscopic adjustable gastric banding, Robotic, laparoscopic gastric banding, Gastric balloons, Gastric pacing, Prolongation of life expectancy by bariatric surgery, Who is and who is not a candidate for bariatric surgery, Bariatric surgery is the current treatment of choice for morbid obesity, Bariatric surgery is relatively safe, reverses the co-morbidities of morbid obesity, improves quality of life, increases life expectancy and is cost effective